Sea Spiders of the Genus Colossendeis (Colossendeidae, Pycnogonida) from the Weddell Sea and Adjacent Waters - Elena P. Turpaeva; Alexey C. Rajsky (Журнал Сибирского федерального университета: Серия Биология, 2013)
Seventeen species and five subspecies of Colossendeis were sampled during the expeditions of R/V Polarstern ANT XIII/3 and ANT XVII/3 in 1996 and 2000 in the Weddell Sea. Polytypical species C. megalonyx Hoek, 1881 was frequently met in this collection. Subspecies C. megalonyx megalonyx was numerous; its traits variability is analyzed. An identification key for subspecies of C. megalonyx has been proposed. Based on the distribution of species and subspecies of Colossendeis as well as intraspecific variability, it is assumed that it is in the Weddell Sea, with its complicated hydrology and relief features, that the speciation of the genus takes place. Representatives of Colossendeis from the Weddell Sea are found now in the Atlantic, the Pacific and the Indian Oceans